Predictors of inadequate weight loss after laparoscopic sleeve gastrectomy - Osama F.I.E Almezaien (Wolters Kluwer Medknow Publications, 2022)
Background and aim Laparoscopic sleeve gastrectomy (LSG) has become a popular procedure in the bariatric field in Egypt. However, little is known regarding the prevalence and risk factors of inadequate weight loss (IWL) following this procedure. Thus, we conducted this study to estimate the prevalence of IWL and its predictors after LSG. Patients and methods The data of consecutive 118 obese adults who underwent LSG were reviewed. The collected data included preoperative and intraoperative variables. Our primary outcome was to estimate the prevalence of IWL or failure after LSG (percent of excess weight loss <50), while the secondary outcomes included identifying risk factors or predictors for this unsatisfactory outcome. Results Failure was encountered in 34 patients out of the included 118 cases. Therefore, the prevalence of failure was 28.81%. Older age and higher basal BMI were associated with failure. Sex distribution was comparable between success and failure groups. Obesity-related comorbidities showed no significant difference between the same groups, apart from obstructive sleep apnea, which showed a significant rise in the failure group. Additionally, operative time, bougie size, and distance from pylorus did not show any significant differences between the two groups. Conclusion Older age, higher basal BMI, obstructive sleep apnea, increased number of obesity-related comorbidities, and previous gastric balloon are significant risk factors for IWL following LSG. Another bariatric procedure (mainly malabsorptive) should be offered for these high-risk groups.